Wild Times at the Bed & Biscuit - Carris, Joan Davenport; Jones, Noah (Noah Z.) (Somerville, Mass. : Candlewick Press, 2009)
When Grampa Bender temporarily takes in some wounded wild animals, Sir Walter, the Scottie, decides he would prefer to be wild and free as well.
Keywords: Veterinarians -- Fiction; Domestic animals -- Fiction; Wild animals -- Fiction